Effect of replacing fish meal with crystalline amino acids on growth performance of nursery pigs from 15 to 25 lb - Nemechek, J.E.; Usry, J.; Tokach, Michael D.; Goodband, Robert D.; DeRouchey, Joel M.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 282 nursery pigs (PIC TR4 × 1050, initially 16.1 lb, 3 d postweaning) were used in a 28-d growth trial to evaluate the effects of replacing fish meal with crystalline amino acids on growth performance. Pigs were allotted to 1 of 6 dietary treatments with 7 replications per treatment. There were 5 replications with 7 pigs per pen and 2 replications with 6 pigs per pen. Pigs and feeders were weighed on d 0, 7, 14, 21, and 28 to calculate ADG, ADFI, and F/G. A 2-phase diet series was used, with treatment diets fed from d 0 to 14 and a common diet fed from d 14 to 28. All diets were in meal form. For the 6 dietary treatments, the fish meal was included at: 4.50, 3.60, 2.70, 1.80, 0.90, and 0.00% respectively. Crystalline lysine, methionine, threonine, tryptophan, isoleucine, and valine all increased as fish meal decreased to maintain minimum amino acid ratios. Also, increasing amounts of glutamine and glycine were used in diets containing 3.60% to 0.00% fish meal to maintain a lysine-to-CP ratio. From d 0 to 14, there was no difference (P > 0.29) in ADG, ADFI, or F/G as the level of fish meal decreased and crystalline amino acids increased. From d 14 to 28 (common diet period), no clear effects (P > 0.09) on growth performance were detected. Overall (d 0 to 28), there was no difference (P > 0.16) in ADG or ADFI. For F/G, a quadratic effect (P < 0.04) was detected, which was the result of small improvements in F/G at the intermediate fish meal levels (2.70 and 1.80). In conclusion, these data suggest that crystalline amino acids, when balanced for minimum amino acid ratios, can be used to replace fish meal in diets for 15- to 25-lb pigs.
Keywords: Swine; Fish meal; Crystalline amino acids; Amino acid requirements